Intramuscular Fat Influences Neuromuscular Activation of the Gluteus Medius in Older Adults - Lanza, Marcel B.; Ryan, Alice S.; Gray, Vicki; Perez, William J.; Addison, Odessa (Frontiers in Physiology, 2020)
The amount of tissue between the muscle and surface electromyography (sEMG) electrode influences the sEMG signals. Increased intramuscular adipose tissue (IMAT) of the hip abductor muscles negatively impacts balance in older individuals, but it is unknown if this is related to the ability to activate the muscles. The aim of this preliminary study was to investigate the influence of gluteus medius (GM) IMAT on sEMG amplitude during maximal voluntary isometric contractions (MVIC) of the hip abductors in older adults. We recruited 12 healthy community-dwelling older adults that underwent a spiral computerized tomography scan. High density lean (HDL), IMAT, and subcutaneous adipose tissue (SUBFAT) cross-sectional area of the GM were assessed. sEMG signal from the GM was recorded while participants performed an MVIC of the hip abductors. There was a negative correlation between GM activation and IMAT (r=-0.58, P=0.046), and also SUBFAT (r=-0.78, P=0.002) and a positive correlation with HDL (r=0.73, P=0.006). When controlling for SUBFAT, the partial correlations demonstrated a consistent negative correlation between GM activation and IMAT (r=-0.60, P=0.050) but no relationship with HDL. The current results are important for helping to interpret the results from sEMG by accounting IMAT. In conclusion, the neuromuscular activation of the GM may be reduced by the quantity of intramuscular adipose tissue.